Noncanonical action of circadian clock genes controls winter diapause entry via the NuA4/TIP60 complex in Harmonia axyridis - Qiao Gao; Yi-Fei Dai; Yu-Lian Zhao; Xue Li; Hao-Min An; Kirst King-Jones; Jia-Lu Wang; Xiao-Ping Wang; Wen Liu (Proceedings of the National Academy of Sciences, 2025)
To adapt to seasonal changes, many animals, particularly insects, enter a dormancy-like condition known as diapause, which is primarily accomplished by sensing photoperiodic signals. The circadian clock, which is driven by positive regulators Clock (CLK) and Cycle (CYC), and negative regulators Period and Timeless, is thought to mediate this response. However, it remains unclear whether diapause induction involves a canonical rhythmic mechanism or occurs independently of their traditional roles in timekeeping. Using the ladybug Harmonia axyridis as a model for short-day-induced winter diapause, we demonstrate that knockdown of Clk and cyc , but not per or tim , disrupted entry into reproductive diapause. This finding demonstrated that Clk-cyc regulates diapause independently of per and tim . We further show that the DNA methyltransferase 1-associated protein 1 (DMAP1)-mediated Nucleosome Acetyltransferase of H4 (NuA4)/TIP60 histone acetyltransferase complex impinges on diapause regulation by acting simultaneously as a downstream effector and a physical interactor of CLK-CYC. Application of the juvenile hormone (JH) receptor agonist methoprene effectively rescued the diapause phenotypes caused by Clk , cyc , and dmap1 knockdowns, highlighting the central role of the CLK-CYC-NuA4/TIP60 complex in JH production. Additionally, using a corpora allata (CA)-specific driver in Drosophila melanogaster , we demonstrate that this complex functions locally in the CA to mediate JH biosynthesis. Collectively, our findings identify a previously unrecognized pathway by which circadian clock proteins interact with an epigenetic regulator to specifically govern JH biosynthesis in a critical endocrine tissue, thereby regulating diapause entry independently of canonical circadian clock mechanisms.